Lifting the burden: fundamental tax reform and U.S. economic growth - Dale W. Jorgenson; Kun-Young Yun (National Bank of Belgium, 2002)
This paper presents a comprehensive treatment of the cost-of-capital approach for analyzing the economic impact of tax policy. This approach has provided an intellectual impetus for reforms of capital income taxation in the United States and around the world. The most dramatic example is the Tax Reform Act of 1986 in the United States. In this landmark legislation the income tax base was broadened by wholesale elimination of tax preferences for both individuals and corporations. Revenues generated by base broadening were used to finance sharp reductions in tax rates at corporate and individual levels. The cost-of-capital approach presented in this paper shows that important opportunities for tax reform still remain. This approach suggests two avenues for reform. One would retain the income tax base of the existing U.S. tax system, but would equalize tax burdens on all forms of assets as well as average and marginal rates on labor income. Elimination of differences in the tax treatment of all forms of assets would produce gains in efficiency comparable to those from the Tax Reform Act of 1986. Equalization of marginal and average tax rates on labor income would more than double these gains in efficiency. Proposals to replace income by consumption as a tax base were revived in the United States during the 1990's. The Hall-Rabushka Flat Tax proposal would produce efficiency gains comparable to those from equalizing tax burdens on all forms of assets under the income tax. However, a progressive National Retail Sales Tax, collected on personal consumption expenditures at the retail level, would generate gains in efficiency exceeding those from the Flat Tax by more than 50 percent! Equalizing marginal and average rates of taxation on consumption would double the gains from the Flat Tax.
Keywords: 330; Investitionsentscheidung; Kapitalkosten; Kapitalertragsteuer; Körperschaftsteuer; Steuerwirkung; Steuerreform; Öffentliche Ausgaben; Wirtschaftswachstum; Theorie; USA